2020
DOI: 10.3390/cryst10040330
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Ridge Engineering of GaSb for the Integration of InAs/GaSb Heterostructures on 300 mm (001) Si

Abstract: Nano-ridge engineering (NRE) is a novel heteroepitaxial approach for the monolithic integration of lattice-mismatched III-V devices on Si substrates. It has been successfully applied to GaAs for the realization of nano-ridge (NR) laser diodes and heterojunction bipolar transistors on 300 mm Si wafers. In this report we extend NRE to GaSb for the integration of narrow bandgap heterostructures on Si. GaSb is deposited by selective area growth in narrow oxide trenches fabricated on 300 mm Si substrates to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…In addition, we have observed that the PD formation is also strongly correlated with the trench formation and pre-epi cleaning processes. Hence, both the seed deposition parameters as well as the template fabrication must be further optimized to reduce the MT density to below 0.2 μm −1 –0.5 μm −1 [ 22 ]. It is important to note that a PD reaching the side and top surfaces of the NR is not accompanied by partial dislocations and, hence, should not significantly impact the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have observed that the PD formation is also strongly correlated with the trench formation and pre-epi cleaning processes. Hence, both the seed deposition parameters as well as the template fabrication must be further optimized to reduce the MT density to below 0.2 μm −1 –0.5 μm −1 [ 22 ]. It is important to note that a PD reaching the side and top surfaces of the NR is not accompanied by partial dislocations and, hence, should not significantly impact the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…Our simulation results show that band tailing due to defect in the source/channel interface is thus of importance on subthreshold performance in the proposed structure. Defects in the GaInAs/GaInSb interface can be of the donor or acceptor type, and their density may vary between 10 5 -10 7 cm -2 [34,35]. In this section, to investigate the effect of defect in the source/channel interface on the performance of Ga 0.8In 0.2As/Ga0.85In0.15Sb VHJLTFT, the donor type defect density is 10 6 cm -2 and the acceptor type defect density is10 7 cm -2 .…”
Section: 3mentioning
confidence: 99%
“…More recently, Kunert et al [62] used a SAE approach to achieve some GaAs and GaSb nano-ridges (NRs) which come out from the cavities with tunable shapes and facets as function of the process conditions (Figure 21a.). These type of NRs can serve as laser diodes structure as well as planar photodetectors.…”
Section: Tdd Reduction By Selective Area Growthmentioning
confidence: 99%